2019
DOI: 10.1186/s12887-019-1596-2
|View full text |Cite
|
Sign up to set email alerts
|

Congenital anomalies prevalence in Addis Ababa and the Amhara region, Ethiopia: a descriptive cross-sectional study

Abstract: Background During the first three months of pregnancy, the developing embryo may be susceptible to external and internal factors, which may lead to structural and functional congenital anomalies. The main objective of this study was to determine the prevalence of congenital anomalies in Addis Ababa and the Amhara region, Ethiopia. Methods A descriptive cross-sectional study was conducted on children 0–17 years of age who visited the 16 selected hospitals in Addis Ababa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 57 publications
5
67
1
Order By: Relevance
“…However some studies, such as those in Irak, India, Turkey and Ethiopia [20,[25][26][27], reported that neurological malformations ranked first with higher prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…However some studies, such as those in Irak, India, Turkey and Ethiopia [20,[25][26][27], reported that neurological malformations ranked first with higher prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the current work is the first systematic review and meta-analysis that explored the prevalence of NTDs and associated factors among children in Ethiopia. After intense searching, data were explored and analyzed from a total of 15 studies 20,[23][24][25][26][27]29,31,32,[36][37][38][39][40][41] conducted in different regions of the country. From these studies, 10 studies 23,24,26,27,29,31,[36][37][38][39] were used to compute the pooled prevalence of NTDs and 6 studies 20,25,26,32,40,41 were used for identifying the risk factor of NTDs.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies were conducted in the central and northern part of the country. All studies were cross-sectional studies 23,24,26,27,29,31,[37][38][39] except a cohort study conducted in Tigray. 36 All of the studies were conducted Abbreviations: OR, odds ratio; CI, confidence interval; BMI, body mass index; NA, not applicable; DD, dietary diversity; BF, breast feeding; PX, pregnancy.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…One such country with high rates of congenital malformation is Ethiopia. In central and north-west Ethiopia, the proportion of congenital anomaly was 199 per 10,000 children who visited the hospitals [18]. This is not surprising as evidence indicated that the highest numbers of birth defects occurred in low and middleincome countries where environmental teratogenic risk factors were more problematic as compared to highincome countries [2,19].…”
mentioning
confidence: 94%